2019
DOI: 10.1021/acs.macromol.9b01320
|View full text |Cite
|
Sign up to set email alerts
|

Chain Conformation, Molecular Dynamics, and Thermal Properties of Poly(n-methylene 2,5-furanoates) as a Function of Methylene Unit Sequence Length

Abstract: Poly(n-methylene 2,5-furanoates) is a family of biobased polymers with outstanding gas barrier and mechanical properties and with the potential to frame the future in certain applications (e.g., food packaging, fibers, and engineering thermoplastics). Herein, we used combined efforts by density functional theory calculations and experiments to explore in detail the conformational properties, the thermodynamics, and the molecular dynamics in the poly(n-methylene 2,5-furanoate) series as a function of n in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
92
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 59 publications
32
92
2
Order By: Relevance
“…In fact, this result is quite interesting due to a number of reasons. First, previous reports on different poly(alkylene furanoate)s described the local relaxation as a single-component process, [27,[29][30][31] whose activation energies were similar to those found for our β 1 contributions. Since the presence of the β 2 component depends on the thermal history of the samples, the absence of this relaxation in previous works can be linked to the different thermal protocols used.…”
Section: Local Relaxationssupporting
confidence: 87%
See 4 more Smart Citations
“…In fact, this result is quite interesting due to a number of reasons. First, previous reports on different poly(alkylene furanoate)s described the local relaxation as a single-component process, [27,[29][30][31] whose activation energies were similar to those found for our β 1 contributions. Since the presence of the β 2 component depends on the thermal history of the samples, the absence of this relaxation in previous works can be linked to the different thermal protocols used.…”
Section: Local Relaxationssupporting
confidence: 87%
“…The four polyesters were successfully processed into films by compression molding, and such films were subjected to thermal, diffractometric, mechanical, and gas permeability characterization. The results indicated that glycol subunit length determined the final polymer properties, finding an odd-even trend [31,32]. In detail, the polymers with an odd number of carbon atoms in the glycol subunit showed a lower tendency to crystallize with consequent formation of a less perfect crystalline phase, i.e., they were characterized by a lower melting temperature than the polymers obtained from glycol with an even number of carbon atoms, and they exhibited superior gas barrier performances.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations